IMPLEMENTASI PROGRAM POS BINAAN TERPADU (POSBINDU) LANSIA DI KELURAHAN PUUNDOHO KECAMATAN BAULA KABUPATEN KOLAKA - Taslim Fait; Fetni (Halu Oleo University, 2024)
This research aims to assess and describe the implementation of the Integrated Elderly Development Post (Posbindu) program in Puundoho Village, Baula District, Kolaka Regency. The study utilized a qualitative approach with a descriptive nature. The research was conducted in Puundoho Village, Baula District, Kolaka Regency, and involved informants including the Puundoho Village Head, Puundoho Midwife, Posbindu Cadre, as well as elderly individuals and their families. Both primary and secondary data were utilized in this study. Based on the research findings, organizational indicators reveal that the implementation of the Posbindu Elderly program in Puundoho Village has not been fully effective. Specifically, the program has been less successful in providing information due to the implementing team's focus on data collection regarding the elderly. The results indicate that while the duties of midwives, nurses, and cadres are performed adequately, issues persist in health examinations, such as the additional cost of IDR 20,000 for medical equipment rental. The program’s effectiveness is further hindered by its monthly implementation and a lack of understanding of the tasks and procedures by the community, which affects overall program efficiency.